Emergence and Characterization of a Novel IncP-6 Plasmid Harboring blaKPC–2 and qnrS2 Genes in Aeromonas taiwanensis Isolates - Hu, Xinjun; Yu, Xiao; Shang, Yibing; Xu, Hao; Guo, Lihua; Liang, Yile; Kang, Yixin; Song, Li; Sun, Jifeng; Yue, Feng; Mao, Yimin; Zheng, Beiwen (Frontiers in Microbiology, 2019)
The dissemination of Klebsiella pneumoniae carbapenemases (KPCs) among Gram-negative bacteria is an important threat to global health. However, KPC-producing bacteria from environmental samples are rarely reported. This study aimed to elucidate the underlying resistance mechanisms of three carbapenem-resistant Aeromonas taiwanensis isolates recovered from river sediment samples. Pulsed-field gel electrophoresis (PFGE) and whole genome sequencing (WGS) analysis indicated a close evolutionary relationship among A. taiwanensis isolates. S1-PFGE, Southern blot and conjugation assays confirmed the presence of blaKPC-2 and qnrS2 genes on a non-conjugative plasmid in these isolates. Plasmid analysis further showed that pKPC-1713 is an IncP-6 plasmid with a length of 53,205 bp, which can be transformed into DH5α strain and mediated carbapenems and quinolones resistance. The plasmid backbone of p1713-KPC demonstrated 99% sequence identity to that of IncP-6-type plasmid pKPC-cd17 from Aeromonas spp. and IncP-6-type plasmid: 1 from Citrobacter freundii at 74% coverage. A 14,808 bp insertion sequence was observed between merT gene and hypothetical protein in p1713-KPC, which include the quinolone resistance qnrS2 gene. Emergence of plasmid-borned blaKPC and qnrS2 genes from A. taiwanensis isolates highlights their possible dissemination into the environment. Therefore, potential detection of such plasmids from clinical isolates should be closely monitored.